Synthesis and Characterization of Activated Carbon From Biomass Waste as A Microwave Absorber Material - Nuras, Muhammad Ishaq; Saptari, Sitti Ahmiatri; Tjahjono, Arif; Priambodo, Danang Pamungkas; Haiqal, Amanda (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
Excessive use of electronic technology can result in harmful radiation and electromagnetic interference, which pose risks to human health. To address this issue, researchers developed a material designed to absorb electromagnetic waves. The study focused on synthesizing and characterizing activated carbon derived from biomass waste, including water hyacinth, melinjo seed shells, and chicken eggshells, with the goal of reducing electromagnetic wave interference. The research process involved several key steps: washing the biomass materials, followed by carbonization, activation using a 65% KOH solution, and subsequent characterization of the material. The tests revealed that the activated carbon possessed a porous structure, which is essential for its absorption capabilities. The surface areas measured were 4.378 m²/g for water hyacinth, 2.518 m²/g for melinjo seed shells, and 2.992 m²/g for chicken eggshells. These surface areas are indicative of the material's potential effectiveness. Additionally, the microwave absorption capacities of the activated carbon were recorded as -18.342 dB for water hyacinth, -13.326 dB for melinjo seed shells, and -12.484 dB for chicken eggshells. These findings suggest that the activated carbons are highly effective as microwave absorber materials, with an absorption efficiency ranging between 94% and 98%.Excessive use of electronic technology can result in harmful radiation and electromagnetic interference, which pose risks to human health. To address this issue, researchers developed a material designed to absorb electromagnetic waves. The study focused on synthesizing and characterizing activated carbon derived from biomass waste, including water hyacinth, melinjo seed shells, and chicken eggshells, with the goal of reducing electromagnetic wave interference. The research process involved several key steps: washing the biomass materials, followed by carbonization, activation using a 65% KOH solution, and subsequent characterization of the material. The tests revealed that the activated carbon possessed a porous structure, which is essential for its absorption capabilities. The surface areas measured were 4.378 m²/g for water hyacinth, 2.518 m²/g for melinjo seed shells, and 2.992 m²/g for chicken eggshells. These surface areas are indicative of the material's potential effectiveness. Additionally, the microwave absorption capacities of the activated carbon were recorded as -18.342 dB for water hyacinth, -13.326 dB for melinjo seed shells, and -12.484 dB for chicken eggshells. These findings suggest that the activated carbons are highly effective as microwave absorber materials, with an absorption efficiency ranging between 94% and 98%.